An Iceland-UK interconnector : the ethical dimension of the “Icelink” project - Pieter-Jan Bogaerts 1995- (2021)
The idea to connect Iceland and the UK via an electrical interconnecting cable was first introduced in the 1980s. Although the project, dubbed “Icelink”, has been the subject of debate for over 40 years, the connection is still not a reality despite it having been proven multiple times that there are no technical barriers to its implementation; that it is economically viable; and despite the fact that, in 2016, the two nations came to a mutual understanding about a joint approach to making the cable connection a reality. On the Icelandic side, the main partners were the national power company, Landsvirkjun, Kvika investment bank, and the engineering company Pöyry. There are several reasons for this failure, one important one being that some fundamental circumstances changed the overall context, leading to the postponement, if not abandonment, of the whole project. This thesis looks at the Icelink project from a fresh angle — the ethical perspective, in order to shed some light on what went wrong. The Icelink Project is scrutinised using the Project Ethics Tool (PET) as a framework. The PET identifies four classical ethical concepts — virtue, utility, duty, and rights — which can be used to understand the ethical implications of a project for seven main groups of stakeholders: (1) the project manager, (2) the project team, (3) the project organization, (4) the host society, (5) future generations, (6) animals, and (7) nature. In this model, the first four (1 - 4) can be active decision-making agents, whereas the latter three (5 - 7) can only deal with the consequences of the decisions taken by the former. The main conclusion is that the Icelink Project was generally undertaken according to generally recognised moral principles but that, in some specific areas a more in-depth consideration of ethical perspectives is required Hugmyndin um að tengja Ísland við England með raforkusæstreng kom first form undir lok áttunda áratugarins. Enn þann dag í dag, meira en 40 árum síðar, er strengurinn ekki orðinn að ...